Analog Rice Reduces Weight and Total Cholesterol Levels in Overweight and Hypercholesterolemic Rats - Dewantari, Septiarina Putri; Hairrudin, Hairrudin; Sakinah, Elly Nurus (Jurnal Kedokteran Brawijaya, 2020)
Overweight, whose prevalence is increasing, is caused by unbalanced consumption patterns such as high consumption of fat and can trigger hypercholesterolemia. Analog rice (AR), which has better nutritional content than ordinary rice, is thought to have beneficial effects on health. This study aimed to determine the potential of analog rice in reducing body weight and total cholesterol levels. A total of 24 male Wistar rats were divided into four groups, namely: I) control, II) ordinary rice treatment, III) analog rice 1 treatment (PBA1) and IV) analog rice 2 treatment (PBA2). The control group was given standard feed for 40 days ad libitum. Groups II, III, and IV were given a combination induction of high-fat diet (HFD) for 40 days ad libitum and intraperitoneal injection of streptozotocin (STZ) 35 mg/kg single dose on day 33. All groups were then given the treatment of diet for three weeks according to their respective groups, namely the standard, ordinary rice, analog rice 1, and analog rice 2 feed. Body weight and total cholesterol levels were measured in the pre-induction, post-induction/pre-treatment (pre-test), and post-treatment (post-test). The results of the study showed that the induction of the HFD-STZ combination carried out resulted in a significant increase in body weight and total cholesterol levels. Measurements made after dietary therapy showed that body weight and total cholesterol levels in the I and II groups did not change significantly, whereas those in the III and IV groups decreased significantly (p<0.05). This study concluded that the administration of analog rice could reduce body weight and total cholesterol levels in overweight and hypercholesterolemia rats.Â